Approximate Solutions of One Abstract Cauchy Problem - Городецький, Василь Васильович; Мартинюк, Ольга Василівна (Springer, 2021)
We find approximate solutions of the Cauchy problem for a differential-operator equation of hyperbolic type with degeneration in a Hilbert space. In terms of these approximations, we give a characteristic of the Gevrey classes for a nonnegative self-adjoint operator.
Keywords: Cauchy problem, differential-operator equation, nonnegative self-adjoint operator